Risk taking, preferences, and beliefs: Evidence from Wuhan - Di Bu; Tobin Hanspal; Yin Liao; Yong Liu (Leibniz Institute for Financial Research SAFE, 2021)
We study risk taking in a panel of subjects in Wuhan, China - before, during the COVID-19 crisis, and after the country reopened. Subjects in our sample traveled for semester break in January, generating variation in exposure to the virus and quarantine in Wuhan. Higher exposure leads subjects to reduce planned risk taking, risky investments, and optimism. Our findings help unify existing studies by showing that aggregate shocks affect general preferences for risk and economic expectations, while heterogeneity in experience further affect risk taking through beliefs about individuals' own outcomes such as luck and sense of control.
Keywords: G50; G51; G11; D14; G41; 330; COVID-19; Risk taking; Beliefs; Formative experiences; Expectations; China